STRATEGI PENGELOLAAN KEUANGAN ONLINE SHOP UNTUK KEBERLANGSUNGAN USAHA (STUDI KASUS PADA ONLINE SHOP KPSTUFF) - Fahrani, Riska Fitri; Yudiantoro, Deny (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.11.TAHUN.2022DO - 10.24843/EEB.2022.v11.i11.p04, 2022)
Online businesses have been widely encountered and run by anyone not limited by age. One of the important things in a business is how the financial management is carried out, because good financial management is able to help a business progress and develop. This study aims to determine the financial management that has been carried out by the owner of the KpStuff online shop and how the sustainability of the online shop business in terms of the application of financial management. This research is a qualitative type, data obtained through interviews with business owners as resource persons. The results showed that the financial management carried out by the online shop KpStuff is still simple but now it is better because it has detailed every transaction made. Therefore, it is recommended to deepen the understanding of good financial management more broadly and thoroughly.